A Planning Model for Construction Minerals - Bishko, Donald; Wallace, William A. (Management Science, 1972)
The problem of allocating construction minerals is rarely considered by those who plan the destiny of our urban environment. The purpose of this research is: (1) to delineate in dollar terms the magnitude of the result of not planning for the consumption of construction minerals, and (2) to develop a computer simulation model which will provide planners with an indication of the effects of decisions. affecting these resources. Construction mineral aggregates (sand, gravel, and crushed stone) are among the earth's most plentiful, yet are rapidly being rendered inaccessible in those areas which need them most. They are characterized by a low intrinsic value, a high bulk, and a delivered price which is very sensitive to the transportation cost associated with moving them from the quarries to their points of demand, It is ironic that the cities which create the demands for mineral aggregates are, at the same time, preventing their extraction by being built over them or by legally limiting their use through zoning restrictions. The simulation model which has been developed enables the planner to investigate the effects of various zoning strategies. It allows him to investigate the results of limiting individual operations and to force the removal of material from a site before it is covered by urban development. It does not attempt to search for decisions which yield “optimal” solutions; rather it indicates the results, over a (simulated) time period, of various planning strategies, thus providing the planner with greater insight into the effects of the decisions that he alone can make.